Accumulating subcultural capital through sport event participation: The AFL International Cup. Issue 3 (June 2018) - Fairley, Sheranne; O'Brien, Danny
Highlights: National representation provides a deeper sense of attachment with the sport. Liminal space led to meeting people from other countries with shared interest in AFL. Engaging with the sport subculture led to a deeper sense of engagement with the AFL. Sense of authenticity was felt through playing regulation matches in the home country. Deeper subcultural connection creates potential for sport advocacy in home countries. Abstract: In this study, the authors use participant interviews to examine how participating in an international event enabled the accumulation of subcultural capital. The authors conducted interviews with players ( N  = 9) in the Australian Football League (AFL) International Cup from Canada, USA, New Zealand, and Ireland. The AFL International Cup created a liminal state offering individuals with opportunities for: (a) national representation; (b) international competition and comparison; (c) cross-cultural learning and interaction; (d) sport subcultural engagement; and, (d) authentic game experiences. The resulting experience enabled participants a deeper connection with the sport subculture, which created the potential for sport advocacy in their home countries. Results will assist international sport event hosts in creating meaningful participant experiences that facilitate deeper personal attachments to the sporting subculture.